miRNA profile in ovarian cancer - Ghafouri-Fard, Soudeh; Shoorei, Hamed; Taheri, Mohammad (Experimental and molecular pathology, 2020)
Ovarian cancer is a gynecological cancer with high mortality and a heterogeneous nature which complicates its early detection and primary prevention. Numerous studies have evaluated expression profile microRNAs (miRNAs) in tissue and serum samples of ovarian cancer patients to find appropriate biomarkers for this malignancy. Functional experiments also verified the oncogenic or suppressor effects of a number of miRNAs. miRNAs exert their role through degradation or inhibition of translation of the target mRNA. Through this regulatory function, they modulate numerous cellular processes which are ultimately associated with carcinogenesis. A number of miRNAs including miR-135a-3p, miR-200c, miR-216a and miR-340 regulate epithelial-mesenchymal transition program thus modulate invasiveness of ovarian cancer cell. Others have been shown to regulate some fundamental pathways in carcinogenesis such as mTOR and PI3K/AKT pathways. Such vast area of function of miRNAs in ovarian cancer has suggested them as putative therapeutic options for future years. In this review, we summarize the recent findings regarding the role of miRNAs in ovarian cancer pathogenesis, their application as biomarkers and the future perspectives of this research area.